Possibilities and limits of the Implementation of the Policy of EU in Central Asia - L. Gusev (Международная аналитика, 2016)
In this paper the author considers policy of the European Union in the Central Asia. The author analyzes an updated EU strategy for the Central Asia and emphasizes its pragmatism, based on individual economic interests of the Central Asian countries in promoting bilateral relations. In the offered paper is also considered the evolution of the EU policy in the Central Asia.